Exploring the interactome of the Staphylococcus aureus sRNA Srn_9342 identified a complex formation with RNAIII leading to the modulation of δ-hemolysin expression - Julie Bronsard; Chloé Silard; Julie Legros; Noëlla Germain-Amiot; Marc Hallier; Yoann Augagneur (BMC Microbiology)
Abstract Background Staphylococcus aureus is a major pathogen responsible for a variety of infections. It expresses a wide range of factors to precisely coordinate gene expression in response to the ever-changing conditions. Among them, regulatory RNAs appear as key players of post-transcriptional and translational regulations. Here, we investigated the role of Srn_9342, a sRNA candidate previously identified in a cluster of five srna genes in Newman strain. Results We showed that Srn_9342 is expressed under two isoforms of different lengths (Srn_9342S and Srn_9342L) whose transcript levels are divergent as a function of growth phase with Srn_9342S being expressed at low cell-density, then being substituted by Srn_9342L at high cell-density. Using MS2-Affinity Purification Coupled with RNA Sequencing, we searched for RNA molecular partners of both Srn_9342S and Srn_9342L. Interestingly, we found that Srn_9342S was mainly bound to sRNAs whereas the expression of Srn_9342L led to the enrichment of mRNAs often linked with transport and metabolism. Among the sRNAs identified, the master regulator of virulence RNAIII appeared as an attractive partner. Using various constructs, we showed that the 5’ end of Srn_9342 specifically binds the 3’ end of RNAIII with high affinity in vitro, and that Srn_9342 mitigate RNAIII transcript level and stability. Finally, we report that the deletion of srn_9342 modulates the expression of the RNAIII encoded toxin δ-hemolysin and hemolytic activity, suggesting that the binding of Srn_9342 onto RNAIII may induce structural changes of RNAIII, and hence expression of the toxin. Conclusions Overall, we showed that Srn_9342 has an unusual pattern of expression and that uncovering its targetome suggests a potential role in S. aureus virulence.